Evaluation of the protective effectiveness of gloves from occupational exposure to 2-methoxyethanol using the biomarkers of 2-methoxyacetic acid levels in the urine and plasma. Issue 8 (16th July 2004) - Chang, H-Y; Lin, C-C; Shih, T-S; Chan, H; Chou, J-S; Huang, Y-S
Abstract : Aims: To evaluate the protective effectiveness of gloves from occupational exposure to 2-methoxyethanol (2-ME); and to examine the association of 2-methoxyacetic acid (MAA) in urine and plasma collected simultaneously from low 2-ME exposure and high 2-ME exposure workers in a semiconductor copper laminate circuit board manufacturing plant. Methods: Eight hour time weighted breathing zone monitoring was performed to verify the 2-ME exposure classification between workers in regular and special operations. Urine and plasma samples were simultaneously collected from 74 exposed and 80 non-exposed workers. MAA concentrations in the urine (UMAA) and plasma (PMAA) were measured using previously published methods. Three types of gloves worn by workers (cotton, rubber, and no gloves) were recorded by direct observations in the workplace and validated by person-to-person interview. Protective effectiveness indices (PEI) were used to evaluate the glove effectiveness. Results: There was no detectable 2-ME/MAA in the air, or in urine and plasma samples in non-exposed workers. The average UMAA and PMAA in special operations were 72.63 mg/g Cr. and 29.72 mg/l, significantly higher than values in regular operations (5.44 mg/g Cr. and 2.58 mg/l, respectively). PMAA showed satisfactory correlation to UMAA in all participants from both regular and special operations. The rubber gloves provided significant reduction in 2-ME uptake, whereas cotton gloves provided little protection with fluctuating effectiveness, based on PEI estimates. Conclusions: PMAA, similar to UMAA, could serve as a specific biomarker for 2-ME exposure. Wearing impermeable rubber gloves during high risk tasks can reduce major 2-ME exposure. Other improvements, including engineering control, should be provided to diminish worker exposure to 2-ME in occupational environments.